2006
DOI: 10.1007/s00299-006-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance of transgenic potato plants expressing both superoxide dismutase and ascorbate peroxidase in chloroplasts against oxidative stress and high temperature

Abstract: Oxidative stress is a major damaging factor for plants exposed to environmental stresses. In order to develop transgenic potato plants with enhanced tolerance to environmental stress, the genes of both Cu/Zn superoxide dismutase and ascorbate peroxidase were expressed in chloroplasts under the control of an oxidative stress-inducible SWPA2 promoter (referred to as SSA plants). SSA plants showed enhanced tolerance to 250 microM methyl viologen, and visible damage in SSA plants was one-fourth that of non-transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 27 publications
4
115
0
1
Order By: Relevance
“…Furthermore, increases in SOD expression are not sufficient to counteract oxidative damage and necrosis: transgenic SOD-overexpressing tobacco that is tolerant to necrosis caused by high light intensity and low temperature, also displays elevated levels of endogenous APX (Gupta et al, 1993). Also, transgenic tobacco or potato that simultaneously overexpress a SOD and an APX gene show enhanced tolerance to necrosis caused by the herbicide paraquat in comparison to transgenic plants that overexpress either SOD or APX (Kwon et al, 2002;Tang et al, 2006). Moreover, simultaneous overexpression of SOD, APX and DHAR in chloroplasts is more effective in inducing tolerance to paraquat and salt treatments, as compared with single or double transformants (Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increases in SOD expression are not sufficient to counteract oxidative damage and necrosis: transgenic SOD-overexpressing tobacco that is tolerant to necrosis caused by high light intensity and low temperature, also displays elevated levels of endogenous APX (Gupta et al, 1993). Also, transgenic tobacco or potato that simultaneously overexpress a SOD and an APX gene show enhanced tolerance to necrosis caused by the herbicide paraquat in comparison to transgenic plants that overexpress either SOD or APX (Kwon et al, 2002;Tang et al, 2006). Moreover, simultaneous overexpression of SOD, APX and DHAR in chloroplasts is more effective in inducing tolerance to paraquat and salt treatments, as compared with single or double transformants (Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Aono et al (1995) crossed transgenic tobacco plants overexpressing SOD or GR and demonstrated a higher level of tolerance to MV-induced oxidative stress in the hybrids, compared to that of either parent. Similarly, SOD and APX have proven an effective combination in transgenic tobacco (Kwon et al 2002;Kim et al 2005), potato (Tang et al 2006) and tall fescue (Lee et al 2007a). In one study with tobacco (Lee et al 2007b) three components of the ROS defence network (SOD, APX and DHAR) were shown to provide further improvements in tolerance to salinity and MV, in comparison with plants over-expressing only the first two of these.…”
Section: Introductionmentioning
confidence: 99%
“…Although several efforts to improve potato quality and resistance to pathogens have been carried out, efforts to improve potato with enhanced tolerance to abiotic stresses through molecular breeding technologies have been limited , Tang et al 2006. In particular, few researchers have integrated genes for antioxidative enzymes into potato plants.…”
Section: Introductionmentioning
confidence: 99%